2017
DOI: 10.1167/iovs.17-21675
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Lens Opacity on SD-OCT Retinal Nerve Fiber Layer and Bruch's Membrane Opening Measurements Using the Anatomical Positioning System (APS)

Abstract: Citation: Mauschitz MM, Roth F, Holz FG, Breteler MMB, Finger RP. The impact of lens opacity on SD-OCT retinal nerve fiber layer and Bruch's membrane opening measurements using the anatomical positioning system (APS). Invest Ophthalmol Vis Sci. 2017;58:280458: -280958: . DOI:10.1167 PURPOSE. To evaluate the impact of lens opacity on retinal nerve fiber layer thickness (RNFLT) and Bruch's membrane opening (BMO) measurements.METHODS. Fifty-nine randomly selected patients without any other relevant ocular pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…They suggested that “optic disc cupping reversal” following the relative ocular hypotony after FLALS might have some tissue-expanding effect similar to that observed after glaucoma surgery, causing the postoperative increase in BMO-MRW. Although Mauschitz et al [ 12 ] reported that RNFLT, BMO area, and BMO-MRW, taken by SD-OCT, remained unchanged after cataract surgery, they differ from our study in that they performed OCT examination on the 1st postoperative day and conducted only on normal subjects.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…They suggested that “optic disc cupping reversal” following the relative ocular hypotony after FLALS might have some tissue-expanding effect similar to that observed after glaucoma surgery, causing the postoperative increase in BMO-MRW. Although Mauschitz et al [ 12 ] reported that RNFLT, BMO area, and BMO-MRW, taken by SD-OCT, remained unchanged after cataract surgery, they differ from our study in that they performed OCT examination on the 1st postoperative day and conducted only on normal subjects.…”
Section: Discussioncontrasting
confidence: 89%
“…Kim et al [ 20 ] reported a significant change in the signal strength values and RNFLT measurements 8 weeks after cataract extraction. The ΔRNFLT and Δsignal strength can be explained by the fact that light attenuation and light scattering induced by cataract might cause the change in RNFLT after cataract surgery [ 12 ]. Mwanza et al [ 15 ] showed that cataract may reduce RNFLT measurements on OCT images and therefore these measurements should be interpreted with caution, especially in eyes with advanced cataract where SS is much attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This holds true for the LQAF and PNS measurements as well. Mauschitz and colleagues, when assessing the impact of lens opacity on retinal nerve fibre layer measurements, used the raw densitometry values of Scheimpflug imaging rather than the PNS 28. Raw values might perform better than an ordinal-scaled score for image quality correlation as well.…”
Section: Discussionmentioning
confidence: 99%